Art is Life : Project '93 - '94 - Tomasinelli, Vezio; Associazione Velan, Torino (Torino : Marco Noire Editore, 1993)
Abate, Gianantonio ; Accardi, Carla ; Adams, Dennis ; Allington, Edward ; Alviani, Getulio ; Andre, Carl ; Antonakos, Stephen ; Aprile Ronda, Omar ; Arcangeli, Maurizio ; Armenia, Giuseppe ; Armleder, John ; Arnese, Dino ; Aschieri, Guglielmo ; Astore, Salvatore ; Barclay, Per ; Barni, Roberto ; Baruchello, Gian Franco ; Beckman, Ford ; Benetti, Mauro ; etc.
Art is Life : Project '93 - '94. Organizzazione: Associazione Velan, Torino. The art works exposed at the Exhibition Art is Life, that will tour in Europe for the '93 and '94 and here presented. Museo dell'Automobile, Torino ; Sierkunst Museum, Gent ; Ministère des Affaires Culturelle, Le "Tutesall", Lussemburgo ; Sotheby's, Londra ; PMMK Musem, Oostend ; Sotheby's, Italia
boek